Genome‐resolved metagenomics of a bioremediation system for degradation of thiocyanate in mine water containing suspended solid tailings. Issue 3 (19th February 2017) - Rahman, Sumayah F.; Kantor, Rose S.; Huddy, Robert; Thomas, Brian C.; van Zyl, Andries W.; Harrison, Susan T.L.; Banfield, Jillian F.
Abstract: Thiocyanate (SCN − ) is a toxic compound that forms when cyanide (CN − ), used to recover gold, reacts with sulfur species. SCN − ‐degrading microbial communities have been studied, using bioreactors fed synthetic wastewater. The inclusion of suspended solids in the form of mineral tailings, during the development of the acclimatized microbial consortium, led to the selection of an active planktonic microbial community. Preliminary analysis of the community composition revealed reduced microbial diversity relative to the laboratory‐based reactors operated without suspended solids. Despite minor upsets during the acclimation period, the SCN − degradation performance was largely unchanged under stable operating conditions. Here, we characterized the microbial community in the SCN − degrading bioreactor that included solid particulate tailings and determined how it differed from the biofilm‐based communities in solids‐free reactor systems inoculated from the same source. Genome‐based analysis revealed that the presence of solids decreased microbial diversity, selected for different strains, suppressed growth of thiobacilli inferred to be primarily responsible for SCN − degradation, and promoted growth of Trupera, an organism not detected in the reactors without solids. In the solids reactor community, heterotrophy and aerobic respiration represent the dominant metabolisms. Many organisms have genes for denitrification and sulfur oxidation, but only one Thiobacillus sp. in the solids reactor has SCN − degradation genes. The presence of the solids prevented floc and biofilm formation, leading to the observed reduced microbial diversity. Collectively the presence of the solids and lack of biofilm community may result in a process with reduced resilience to process perturbations, including fluctuations in the influent composition and pH. The results from this investigation have provided novel insights into the community composition of this industrially relevant community, giving potential for improved process control and operation through ongoing process monitoring. Abstract : Thiocyanate (SCN − )‐degrading microbial communities have been studied, using bioreactors fed synthetic wastewater. The inclusion of suspended solids in a thiocyanate‐degrading bioreactor, during the development of the acclimatized microbial consortium, led to the selection of an active planktonic microbial community. Here, we characterized the microbial community in the thiocyanate‐degrading bioreactor that included solid particulate tailings and determined how it differed from the biofilm‐based communities in solids‐free reactor systems inoculated from the same source.